The Anti-proliferative Activity of GnRH Through Downregulation of the Akt/ERK Pathways in Pancreatic Cancer - Suo, Linna; Chang, Xiaocen; Xu, Na; Ji, Hongmei (Frontiers in Endocrinology, 2019)
Gonadotropin-releasing hormone (GnRH) has been demonstrated to exert anti-proliferative effects on various tumour cells in ovarian, endometrial, bladder, and prostate cancer as a part of the autocrine system. In addition, the expression of GnRH and its receptor has been identified in breast cancer and non-reproductive cancers, such as pancreatic cancer and glioblastoma. Previous studies have reported abnormal GnRH expression in several malignant tumours, suggesting that GnRH and its receptor might be essential for tumourigenesis. In the present study, we attempted to clarify the mechanisms underlying GnRH function in cell proliferation in pancreatic cancer. Our results indicated that GnRH expression might be associated with the malignancy of pancreatic cancer. We found that GnRH overexpression induces cell apoptosis through activation of the Bcl-2/Bax pathway and that autophagy was involved in the GnRH-mediated apoptosis in pancreatic cancer cells. Further investigation showed that inhibition of GnRH can promote tumour invasion and migration through upregulation of MMP2 expression in pancreatic cancer cells. Moreover, our results indicated that GnRH can regulate the Akt/ERK1/2 pathways to promote cell proliferation by inhibiting cell apoptosis in pancreatic cancer cells. Therefore, our findings revealed that regulation of GnRH expression might be important for tumourigenesis in pancreatic cancer and is a potential target for treatment of patients with pancreatic cancer.